Physical Exercise Affects Quality of Life and Cardiac Autonomic Modulation in Patients With Chronic Kidney Failure Submitted to Hemodialysis: A Randomized Clinical Trial. Issue 3 (June 2022) - Pereira, Ana Beatriz Nunes; Santana, Larissa Lopes; Rocha, Letícia De Barros; Cunha, Katiane Da Costa; Rocha, Larissa Salgado De Oliveira; Santos, Marcio Clementino De Souza; Normando, Valéria Marques Ferreira; Torres, Daniel Da Costa; Rocha, Rodrigo Santiago Barbosa
Performing physical exercise during hemodialysis has been debated regarding safety and efficacy for improving life quality for patients with chronic kidney disease (CKD). Thus, we explored the influence of physical exercise during hemodialysis on both autonomic modulation of heart rate and quality of life for patients with CKF in a randomized clinical trial. We randomly allocated participants requiring hemodialysis to an experimental exercise group (EG) and a control no-exercise group (CG) and assessed their quality of life with the Kidney Disease Quality of Life Short Form—KDQOL-SF ™ 1.3 and with Polar RS800CX to monitor their heart rate variability (HRV) before and three months after the end of the exercise intervention. EG participants reported a significant increase in their quality of life ( p = .05, physical function, physical aspects, pain, emotional well-being, emotional function; p = .03, energy and fatigue) and showed HRV improvement ( p = .05, RMSSD, SDNN, and SD2; p = .004, SD1) after three months of exercise. Thus, we recommend supervised physical exercise during hemodialysis for carefully selected patients.